Onboard the M/V R.M. Thorstenson during the 2013 salmon season in Norton Sound just south of Nome, Alaska. The Native fishermen haven't seen our ship in years since they are in such a remote location, this shot was taken of their boats after they boarded our ship for a welcoming reception and tour. - Nguyen, Thai
2013 TSGB, Commercial